(untitled) (Wardah, 2016)
The word ‘Dakwah’ in the Islamic University is not a new word. But for public, it is a new, strange and confused word. And the question of the word is not like what we expected. On the other side, the term communication is more familiar. Though, their assumption refers to the instruments likes telephone, handy talky, etc. Even television, radio and newspaper haven’t categorized as the media for communication. Commonly, from the definition of the two terms – dakwah and communication – have some similarities, yet few differences. Therefore, the usage of the term communicative dakwah can be accepted with no apostrophes. This research will explain about what a communicative dakwah is and its characteristics.